The Implementation of 2013 Curriculum in Mathematics Learning at SMA Muhammadiyah 3 Tangerang - Nisvu Nanda Saputra; Rika Sukmawati (SAINTIS Publishing, 2019)
The objectives in this study are 1) Describe the implementation of the 2013 curriculum in mathematics learning, 2) Formulate what factors support and hinder the implementation of the 2013 curriculum. This study is a type of qualitative research using a descriptive approach. The study subjects were mathematics teachers who taught in class X of SMA Muhammadiyah 3 in Tangerang City. Data collection techniques used are in-depth interviews, observation, documentation. Technical data analysis is done by reducing, presenting data, and verification. The results showed that the X grade mathematics teacher in implementing the 2013 curriculum was still lacking. This can be seen by teachers not compiling RPPs based on the 2013 curriculum. As a result, the learning process is not in accordance with the demands according to 2013 curriculum references. Factors that prevent teachers from implementing the 2013 curriculum are teachers who have not attended 2013 curriculum training, teachers have not joined and are taking part in routine activities in the city high school MGMP routine Tangerang, schools have not facilitated 2013 curriculum training activities and the lack of existing infrastructure in the school environment to support the implementation of the 2013 curriculum